Cultural Survival, Continuance and the Oral Tradition: Mendu Theatre of the Riau Islands Province, Indonesia - Karen Kartomi Thomas (Graduate School of Institut Seni Indonesia Yogyakarta, 2015)
This article seeks to describe Mendu theatre that is performed in Sedanau, Natuna regency (kabupaten) of one of Indonesia’s newest provinces, the Riau Island. 1 Once popular at the turn of the 20 th century and in the 1970s and 1980s, there were local Mendu groups in every village of Natuna in parts of northern and eastern Bunguran island, and other smaller islands such as Sedanau, Pulau Tiga, Karempak, Midai, Siantan, and Anambas (K.S. Kartomi 1986; Illyassabli, 2013; Akib 2014). The oral tradition keeps a people’s culture alive across generations by performing episodes from memory. Mendu theatre episodes express and reinstate the cultural values of the Natuna people. Language, culture, customary laws and how the people think are transmitted orally through the arts and through the embodied knowledge of theatre performance practices.